Prevalence and Antibiotic sensitivity of Escherichia coli in Extensive Brackish water Aquaculture Ponds - A.A., Mohamed Hatha; R., Harish; C.M., Sumitha (Fishery Technology, 2025)
Prevalence and antibiotic resistance of Escherichia coli in the water and sediment samples of brackish water aquaculture ponds adjacent to Cochin backwaters was analysed. More than 50% of the water samples and more than 80% of sediment samples from all the sampling stations were tested positive for £. coli. Risk assessment of the E. coli strains was carried out using multiple antibiotic resistance (MAR) indexing. Majority of the strains were found to be multiple antibiotic resistant suggesting their origin from high risk sources of contamination such as human where antibiotics are frequently used. While none of the £. coli strains were resistant against amikacin, chloramphenicol, streptomycin and trimethoprim, considerable levels of resistance was encountered against ampicillin, erythromycin, penicillin G and vancomycin. High prevalence of £. coli in the water and sediment samples of this extensive brackish water ponds indicates high degree of faecal pollution of this environment. The high risk nature of the strains warrants efficient post harvest and processing measures to avoid health risk to consumers.